Cinnamon improves glucose and lipids of people with type 2 diabetes - Khan, Alam; Jadoon, Mahpara Safdar; Khattak, Muhammad Muzaffar Ali Khan; Khattak, Khan Nawwaz; Anderson, Richard A. (American Diabetes Association, 2003)
OBJECTIVE— The objective of this study was to determine whether cinnamon improves blood glucose, triglyceride, total cholesterol, HDL cholesterol, and LDL cholesterol levels in people with type 2 diabetes. RESEARCH DESIGN AND METHODS— A total of 60 people with type 2 diabetes, 30 men and 30 women aged 52.2 6.32 years, were divided randomly into six groups. Groups 1, 2, and 3 consumed 1, 3, or 6 g of cinnamon daily, respectively, and groups 4, 5, and 6 were given placebo capsules corresponding to the number of capsules consumed for the three levels of cinnamon. The cinnamon was consumed for 40 days followed by a 20-day washout period. RESULTS— After 40 days, all three levels of cinnamon reduced the mean fasting serum glucose (18–29%), triglyceride (23–30%), LDL cholesterol (7–27%), and total cholesterol (12–26%) levels; no significant changes were noted in the placebo groups. Changes in HDL cholesterol were not significant. CONCLUSIONS— The results of this study demonstrate that intake of 1, 3, or 6 g of cinnamon per day reduces serum glucose, triglyceride, LDL cholesterol, and total cholesterol in people with type 2 diabetes and suggest that the inclusion of cinnamon in the diet of people with type 2 diabetes will reduce risk factors associated with diabetes and cardiovascular diseases.